(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
Poly Methyl Methacrylate resin distinguished by its low impact and fatigue strength, there are many researches that will deal with these situations. In the current study the matrix was heat cured material powder of PMMA was reinforced with peanut and walnut Shells to PMMA base material, which commonly utilize in the applications of denture. these natural powders were added in various weights fraction (4%, 8%, and 12%), and with similar average particle size (53μm) and studied Density and water absorption properties. In this study the method used to prepare the specimens is Hand Lay-Up method. The results showed that the values of density are increased when the weight fractions of both reinforcing natural particles increased and the maximum value was obtained with adding peanut shells powder at (12 wt.%.) (1.206 gm/????????3) for the composite specimens, while the values of water absorption Tests was decreased by increasing the weight fractions of both reinforcing powders peanut and walnut Shells in PMMA resin and The lowest values was obtained by adding peanut shells powder at (12 wt.% P) (0.003 % ).